2023
DOI: 10.1002/nvsm.1796
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing value in healthcare partnerships: A case examining an inter‐organizational relationship in the public and non‐profit sectors

Abstract: Healthcare organizations around the world are striving to find the right balance between using their resources effectively and providing personalized care to patients.Health care is shifting from a reactive, towards a more person-centric approach to improve health outcomes. To achieve quality improvements and efficiencies, health care organizations are forming inter-organizational relationships. Despite the benefits, little is known about how organizations capture value from strategic partnership.In this conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…To address this gap, it is crucial to establish comprehensive evaluation frameworks that scrutinize both the process and outcomes of co-created health services. For instance, Carlini et al (2023) use a value mapping framework to discern various types of value (captured, missed, destroyed and opportunity) in a public-sector health service initiative, emphasizing the potential for negative and unintended consequences when such initiatives are not subject to scrutiny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this gap, it is crucial to establish comprehensive evaluation frameworks that scrutinize both the process and outcomes of co-created health services. For instance, Carlini et al (2023) use a value mapping framework to discern various types of value (captured, missed, destroyed and opportunity) in a public-sector health service initiative, emphasizing the potential for negative and unintended consequences when such initiatives are not subject to scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…The co-creation of service design intends to deliver an innovative service that has value for consumers and service providers. In the context of health care, value refers to the societal benefits derived from services, interventions or programs aimed at enhancing health outcomes and improving the quality of life for individuals, families and communities (Carlini et al , 2023). However, in a review of five major service research journals, researchers found that involvement in the co-creation of services can have both positive and negative outcomes for consumer and service provider participants (Oertzen et al , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%